Emerging digital media, games and simulations: a challenge for open and distance learning - Bidarra, José (2013)
In this article we examine the state-of-the-art research related to digital media in education and evaluate the information concerning a new generation of students that are communityminded and technologically savvy, highlighting the innovative technology behind the new interaction and communication processes, and assessing the challenges for Open and Distance Learning (ODL). Where traditional distance education is based on the completion of carefully graded assignments and tests, today games, simulations and virtual environments may become safe platforms for trial and error experimentation. With games the chance of failure is high, but the cost is low and the lessons are learned immediately and with greater emotional impact. However, these conditions may become more difficult to address when the volume of users increases from small to medium, large or extra-large. Dealing effectively with tens or even hundreds of thousands of students in absentia requires following very sound organizational principles and good technical implementation, systematic monitoring of deviations from established norms, regular audition of users' comments and criticisms, careful analysis of final results. In this emerging scenario, involving digital media, games and simulations, ODL systems must have means of establishing rich connections with each member of the universe of users. In this sense we propose using a virtual space with multiple places, in ways that use the Internet, social applications, games and mobile devices to involve students in pedagogical activities.